1999
DOI: 10.1046/j.1365-3040.1999.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of reserve and newly assimilated carbon in roots and leaf tissues of Lolium perenne during regrowth after defoliation: assessment by 13C steady‐state labelling and carbohydrate analysis

Abstract: The relative significance of the use of stored or currently absorbed C for the growth of leaves or roots of Lolium perenne L. after defoliation was assessed by steady‐state labelling of atmospheric CO2. Leaf growth for the first two days after defoliation was to a large extent dependent on the use of C reserves. The basal part of the elongating leaves was mainly new tissue and 91% of the C in this part of the leaf was derived from reserves assimilated prior to defoliation. However, half of the sucrose in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 29 publications
5
67
0
8
Order By: Relevance
“…Although no definitive arguments have been made with respect to whether post defoliation leaf growth is predominantly limited by carbon or by nitrogen, recent studies suggest that C and N co-regulate leaf growth in general [85], and thus either C or N may play the predominant role depending on prevailing conditions in nitrogen supply and PAR prior to defoliation. Recent studies clearly show that the dependence of leaf growth on non-structural carbon accumulated prior to defoliation is shorter (about 2 days) than previously thought [85,86].…”
Section: Leaf Growth Ratementioning
confidence: 79%
“…Although no definitive arguments have been made with respect to whether post defoliation leaf growth is predominantly limited by carbon or by nitrogen, recent studies suggest that C and N co-regulate leaf growth in general [85], and thus either C or N may play the predominant role depending on prevailing conditions in nitrogen supply and PAR prior to defoliation. Recent studies clearly show that the dependence of leaf growth on non-structural carbon accumulated prior to defoliation is shorter (about 2 days) than previously thought [85,86].…”
Section: Leaf Growth Ratementioning
confidence: 79%
“…No significant differences in total fructose were found in the elongating leaf blades in comparison with the expanded leaf blades (figure 2). In L. perenne, Guerrand et al (1996) and Morvan-Bertrand et al (1999) reported higher fructan contents in the elongating leaves than in expanded leaves. These results suggest that fructose polymers could have functions such as energy supply, unloading of sucrose from phloem and regulation of osmotic potential (Volenec, 1986;Cairns et al, 1991).…”
mentioning
confidence: 89%
“…in this phase, leaf regrowth assumes the highest priority in allocation of current photosynthates, followed by commencement of root regrowth and daughter tiller initiation in L. perenne (Donaghy & Fulkerson 1998;Morvan-bertrand et al 1999) and D. glomerata (Rawnsley et al 2002). This means that following defoliation plants initially replace the removed leaf area and then invest energy into shoot and root growth.…”
Section: Discussionmentioning
confidence: 99%